2019
DOI: 10.1111/jcmm.14898
|View full text |Cite
|
Sign up to set email alerts
|

Platinum‐based combination chemotherapy triggers cancer cell death through induction of BNIP3 and ROS, but not autophagy

Abstract: These days, cancer can still not be effectively cured because cancer cells readily develop resistance to anticancer drugs. Therefore, an effective combination of drugs with different mechanisms to prevent drug resistance has become a very important issue. Furthermore, the BH3-only protein BNIP3 is involved in both apoptotic and autophagic cell death. In this study, lung cancer cells were treated with a chemotherapy drug alone or in combination to identify the role of BNIP3 and autophagy in combination chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The damage to mitochondria could increase the permeability of its membrane, which in turn resulted in the excessive release of ROS and cyto-c. Atezolizumab increased the release of ROS while reducing the content of SOD and T-AOC in OS cells, which in turn caused excessive oxidative stress, leading to lipid peroxidation and DNA damage. Meanwhile, the excessive release of cyto-c could bind to APAF-1 in cytoplasm and thus activate caspase-9, one of the initiators of apoptosis, and eventually activating caspase-3 causing mitochondria-related apoptosis in cells [31][32][33] . The activation of JNK pathway is closely related to the tumor cell apoptosis, especially to the mitochondria-related apoptosis 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The damage to mitochondria could increase the permeability of its membrane, which in turn resulted in the excessive release of ROS and cyto-c. Atezolizumab increased the release of ROS while reducing the content of SOD and T-AOC in OS cells, which in turn caused excessive oxidative stress, leading to lipid peroxidation and DNA damage. Meanwhile, the excessive release of cyto-c could bind to APAF-1 in cytoplasm and thus activate caspase-9, one of the initiators of apoptosis, and eventually activating caspase-3 causing mitochondria-related apoptosis in cells [31][32][33] . The activation of JNK pathway is closely related to the tumor cell apoptosis, especially to the mitochondria-related apoptosis 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was reported to promote the migration, invasion, and metastasis of NSCLC through the LATS2/YAP signaling pathway in a recent study [ 101 ]. Reactive oxygen species (ROS) are the downstream products of oxidative stress and have been identified to be involved in response to anti-cancer therapies in human NSCLC [ 102 , 103 ]. A previous study by Huang et al reported that the activation of YAP increased the accumulation of ROS by downregulating the antioxidant enzyme GPX2 in human lung squamous cell carcinoma [ 104 ].…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
“…The development of chemical agents for BNIP3 targeting could be a prospective strategy to overcome radioresistance acquired during inoperable tumor therapy. In addition to autophagy, BNIP3 participates in cisplatin-induced cell death, including apoptosis [ 78 , 85 ]. Cisplatin treatment increases BNIP3 protein levels; however, its combination with hypoxia reduced BNIP3 in lung cancer cell lines.…”
Section: Bnip3 In Lung Cancermentioning
confidence: 99%
“…The histone deacetylases inhibitor, panobinostat, LBH589, is a promising agent for lung cancer therapy through the impairment of histone deacetylation and subsequent weakening of gene transcription, especially oncogenes. The combination of LBH589 and cisplatin triggers BNIP3 insertion into the mitochondrial membrane by its TM domain, which eventually promotes ROS and potential mitochondrial membrane loss, leading to apoptotic cell death in the lungs [ 85 ]. The molecular design of drugs for the stimulation of BNIP3 TM domain insertion into mitochondria could provide an efficient tool to enhance sensitivity to apoptosis.…”
Section: Bnip3 In Lung Cancermentioning
confidence: 99%